KESESUAIAN LAHAN UNTUK JENIS CENDANA (SANTALUM ALBUM LINN.) DI KABUPATEN ALOR PROVINSI NUSA TENGGARA TIMUR - Hery Kurniawan; Sumardi Sumardi; Eko Pujiono (Environmental Research Center (PPLH) of Udayana University, 2015)
Cendana (Santalum album L.) is an indigenous species of east nusa tenggara (Nusa TenggaraTimor/NTT) which has high economies value. The existency of this species in nature hasalmost extinct due to uncontrolled exploitation. It needs conservation and developmentefforts. The efforts needs data of land suitability endorsement to support the success ofplantation. This research was aimed to set land suitability digital map for cultivatingcendana as guidance in making plan cendana plantation in Alor Regency. The researchused land suitability analysis method by field survey. Purposive sample was determinedbased on land variation by land cover and type of soil. The result showed the large of landsuitability 2 is the largest with 126.810,73 Ha, followed by land suitability 1 with 58.893,2Ha large of area, then land suitability 4 with 20.011,41 Ha, and land suitability 3 with5.664,58 Ha large of area.